2022
DOI: 10.1111/jog.15227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of women's sexual quality of life, depression, and sexual functions in the pregnancy and postpartum periods: A multi‐centered study

Abstract: Aim This multi‐centered, longitudinal, and prospective study aims to identify women's sexual functions, sexual quality of life, and depression and their relationships with each other in the pregnancy and postpartum periods. Methods The participating pregnant women (n = 113) were interviewed six times: once in each trimester, and once in the eighth week third month, and sixth month postpartum. This study was conducted in three regions of Turkey including Marmara, Mediterranean, and Central Anatolia regions. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Women with better sexual functioning showed greater sexual quality of life. Sexual quality of life and functioning both are associated with the sexual dimension, and it seems that sexual functioning through sexual drive and its impact on personal, social, and familial relationships can influence the general quality of life and the sexual quality of life [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with better sexual functioning showed greater sexual quality of life. Sexual quality of life and functioning both are associated with the sexual dimension, and it seems that sexual functioning through sexual drive and its impact on personal, social, and familial relationships can influence the general quality of life and the sexual quality of life [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRISMA = preferred reporting items for systematic reviews and meta-analyses, WOS = Web of Science. Prospective cohort study [20] ---FSFI [10] 2000 Sexual function Clinical trial [21][22][23] Cross-sectional study [18,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] Prospective cohort study [20,[38][39][40][41][42][43][44][45][46][47][48][49] Iranian version of 19-item FSFI [18,[50][51][52] Hungarian version of 19-item FSFI [35] Taiwan version of 19-item FSFI [44,53] The Turkish version of 19-item FSFI [46,54] German version of Female Sexual Function Index (FSFI-d) [38,55] SFQ28 [56] 2002 Sexual health 28-item questionnaire 7 domains of:…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][14][15][16][17] The research conducted by Branecka-Wózniak et al 2 with patients of the pregnancy pathology ward, demonstrated that higher levels of sexual satisfaction in every dimension, were associated with higher level of satisfaction with life and emphasize the need for comprehensive perinatal care and professional sexual counselling. Surucu et al 18 in their study found out, that the sexual dysfunction rates of the participants were high during pregnancy, and their sexual quality of life decreased as the pregnancy months progressed. With different results, the research of Kucukdurmaz et al 19 reported that the sexual dysfunction rate was higher in the first and third trimesters compared to the second trimester.…”
Section: Introductionmentioning
confidence: 94%
“…In this regard, sexual health should be regarded as an important component of general health; effective and accurate guidance is considered to contribute to the maintenance of psychological health and the improvement of women's health. 18 Barriers, which can contribute to a lack of screening for sexual dysfunction, include patient discomfort with sexual topics, scarcity of provider training about sexual medicine, and a perceived shortage of time to address these concerns during health care appointments. 22 To improve the access to information about sexual function and satisfaction during pregnancy, it's important to identify and map the valid, reliable, and specific assessment instruments and their possibilities and limitations to prevent problems, identify women needs, and plan specific health care interventions.…”
Section: Introductionmentioning
confidence: 99%